Factors Related to Reproductive Health Among High School Students in Semarang (Universitas Negeri Semarang, 2018)
Risky behavior on teenager especially on high school students are tend to increase. It has been proved by the fact that in almost 50% teenager in Semarang already having premarital sex.The porpoise of this study is to prove the effect of knowledge, information source, religious understanding, family role, and friend of the same age, education role in school on premarital sexual behavior among high school in Semarang. This study is a cross sectional study with quantitative and qualitative approach with 158 student as population. Simple Random technique sampling was using in this study to determined the method, there are 64 students as sample of this study and there are 9 informants which was determined from purposive sampling. Statistical Analysis which is used in this study is chi square and logistic regression. This study result found that there is effect of knowledge OR=3,66 (p=0,010), information source, religious understanding OR=3, 86(p=0,007, friend of the same age OR=3,14(p=0,023), on premarital sexual behavior among highschool student in Semarang. Variable which have biggest effect is religious understanding in high school student with OR=3,273.